A nearby distractor does not influence hand movements. (September 2021) - Arkesteijn, Kiki; Donk, Mieke; Belopolsky, Artem V.; Smeets, Jeroen B.J.
Abstract: When interacting with the environment, our manual actions are often preceded by an eye movement. This suggests that the processes underlying target selection in hand and eye movements may be coupled. It is known that when a distractor is presented close to a target, the endpoint of an eye movement will be biased towards the distractor. The size of this so-called global effect decreases when more viewing time is available. Here we investigate whether a similar effect is also present in hand movements. If the processes underlying target selection for hand and eye movements are indeed coupled, a similar bias should be present in hand movements as well. To test this, we adopted a classic global effect paradigm but applied it to goal-directed hand movements. We show that the endpoints of hand movements are unbiased for all but one participant, irrespective of the viewing time. These results suggest that the processes underlying target selection for hand movements operate independently from those for eye movements.